1997
DOI: 10.1042/bj3280565
|View full text |Cite
|
Sign up to set email alerts
|

Detection of free radicals produced from the reaction of cytochrome P-450 with linoleic acid hydroperoxide

Abstract: The ESR spin-trapping technique was employed to investigate the reaction of rabbit cytochrome P-450 1A2 (P450) with linoleic acid hydroperoxide. This system was compared with chemical systems where FeSO4 or FeCl3 was used in place of P450. The spin trap 5, 5'-dimethyl-1-pyrroline N-oxide (DMPO) was employed to detect and identify radical species. The DMPO adducts of hydroxyl, O2-., peroxyl, methyl and acyl radicals were detected in the P450 system. The reaction did not require NADPH-cytochrome P-450 reductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…This is followed by radical rebound resulting in the formation and release of the alcohol metabolite (Atkinson and Ingold, 1993; dmd.aspetjournals.org Shaik et al, 2002). The carbon-centered radical is very short-lived and is rapidly hydroxylated and released from the active site as a metabolite much faster than the radical itself can escape from the hydrophobic enzyme active site (Heur et al, 1989;Bowry et al, 1990;Rota et al, 1997). This scenario reflects the metabolism of PCP by P450 2B6 and accounts for the partition ratio for P450 2B6 inactivation by PCP as being 45 (Jushchyshyn et al, 2003), which suggests that the majority of PCP secondary carbons are oxidized and released from the active site as hydroxylated metabolites (M1 and M2).…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by radical rebound resulting in the formation and release of the alcohol metabolite (Atkinson and Ingold, 1993; dmd.aspetjournals.org Shaik et al, 2002). The carbon-centered radical is very short-lived and is rapidly hydroxylated and released from the active site as a metabolite much faster than the radical itself can escape from the hydrophobic enzyme active site (Heur et al, 1989;Bowry et al, 1990;Rota et al, 1997). This scenario reflects the metabolism of PCP by P450 2B6 and accounts for the partition ratio for P450 2B6 inactivation by PCP as being 45 (Jushchyshyn et al, 2003), which suggests that the majority of PCP secondary carbons are oxidized and released from the active site as hydroxylated metabolites (M1 and M2).…”
Section: Discussionmentioning
confidence: 99%
“…To date, nitrone spin-trapping agents, including ␣ -[4-pyridyl-1-oxide] N -tert-butyl nitrone and 5,5 Ј -dimethyl-1-pyroline-N -oxide, have been used to detect these lipid-derived radicals (12)(13)(14)(15)(16)(17). Furthermore, Mason and coworkers (13)(14)(15) established an HPLC/ESR system to identify the resulting radical adducts.…”
mentioning
confidence: 99%
“…In this study, the 4-POBN\octanoic acid and 4-POBN\pentyl radical adducts were detected and identified in the reaction mixture of 13-HPODE with cytochrome c or haematin using HPLC-ESR and HPLC-ESR-MS. Our previous studies have also shown the formation of the octanoic acid and pentyl radicals [23] and Rota et al [10] have also presented homolytic scission for the reaction of cytochrome c with tbutylhydroperoxide [23] and the reaction of cytochrome P450 with 13-HPODE [10]. On the other hand, it is also possible for heterolytic peroxide bond cleavage to result in the formation of the alkoxyl radical, as follows [24][25][26] :…”
Section: Discussionmentioning
confidence: 99%